PENDEKATAN TEKNIK KOMUNIKASI DALAM PENYULUHAN PENGGUNAAN PUPUK ORGANIK BAGI PETANI SAYURAN KANGKUNG DI KELURAHAN MATABUBU KECAMATAN POASIA KOTA KENDARI - Gita R., Sri Utari; Rela, Iskandar Zainuddin; Jayadisastra, Yoenita (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2024)
This study aims to determine and analyze the communication techniques of extension workers in counseling the use of organic fertilizers for farmers, and to know the knowledge of farmers in the use of organic fertilizers in Matabubu Village, Poasia District, Kendari City.This research was conducted in July 2023. The population in the study will be informants, because kale farmers in Matabubu Village amounted to 7 people, as well as 1 extension agent in charge of Matabubu Village. Data collection techniques consist of observation, in-depth interviews, documentation and literature. The focus of the research includes: extension communication techniques (informative communication, persuasive communication and instructive communication), farmers' knowledge during related extension (source/content of organic fertilizer, benefits of organic fertilizer, how to make organic fertilizer and use of organic fertilizer). The analysis used in this research is qualitative descriptive analysis. The results showed that the communication techniques used consisted of informative, persuasive and instructive communication techniques that had been implemented by extension workers. As well as, farmers' knowledge in the use of organic fertilizer for kale vegetables in general have known, but the process of making organic fertilizer, farmers do not know